Using 10Be cosmogenic isotopes to estimate erosion rates and landscape changes during the Plio-Pleistocene in the Cradle of Humankind, South Africa. Issue 96 (July 2016) - Dirks, Paul H.G.M.; Placzek, Christa J.; Fink, David; Dosseto, Anthony; Roberts, Eric
Abstract: Concentrations of cosmogenic 10 Be, measured in quartz from chert and river sediment around the Cradle of Humankind (CoH), are used to determine basin-averaged erosion rates and estimate incision rates for local river valleys. This study focusses on the catchment area that hosts Malapa cave with Australopithecus sediba, in order to compare regional versus localized erosion rates, and better constrain the timing of cave formation and fossil entrapment. Basin-averaged erosion rates for six sub-catchments draining the CoH show a narrow range (3.00 ± 0.28 to 4.15 ± 0.37 m/Mega-annum [Ma]; ±1σ) regardless of catchment size or underlying geology; e.g. the sub-catchment with Malapa Cave (3 km 2 ) underlain by dolomite erodes at the same rate (3.30 ± 0.30 m/Ma) as the upper Skeerpoort River catchment (87 km 2 ) underlain by shale, chert and conglomerate (3.23 ± 0.30 m/Ma). Likewise, the Skeerpoort River catchment (147 km 2 ) draining the northern CoH erodes at a rate (3.00 ± 0.28 m/Ma) similar to the Bloubank-Crocodile River catchment (627 km 2 ) that drains the southern CoH (at 3.62 ± 0.33 to 4.15 ± 0.37 m/Ma). Dolomite- and siliciclastic-dominated catchments erode at similar rates, consistent with physical weathering as the rate controlling process, and a relatively dry climate in more recent times. Erosion resistant chert dykes along the Grootvleispruit River below Malapa yield an incision rate of ∼8 m/Ma at steady-state erosion rates for chert of 0.86 ± 0.54 m/Ma. Results provide better palaeo-depth estimates for Malapa Cave of 7–16 m at the time of deposition of A. sediba . Low basin-averaged erosion rates and concave river profiles indicate that the landscape across the CoH is old, and eroding slowly; i.e. the physical character of the landscape changed little in the last 3–4 Ma, and dolomite was exposed on surface probably well into the Miocene. The apparent absence of early Pliocene- or Miocene-aged cave deposits and fossils in the CoH suggests that caves only started forming from 4 Ma onwards. Therefore, whilst the landscape in the CoH is old, cavities are a relatively young phenomenon, thus controlling the maximum age of fossils that can potentially be preserved in caves in the CoH.